Cyclic behavior and deformation mechanism of superelastic SMA U-shaped dampers under in-plane and out-of-plane loadings. (1st April 2021) - Wang, Bin; Zhu, Songye; Casciati, Fabio; Chen, Kaixin; Jiang, Huanjun
Abstract: This study systematically investigates the cyclic behavior and deformation mechanism of superelastic shape memory alloy U-shaped dampers (SMA-UDs) that are intended for seismic resilient applications. The study first summarized the experimental investigations of a series of SMA-UD component tests under loadings in two directions (i.e. in-plane and out-of-plane directions). Test results demonstrated that SMA-UDs exhibit excellent self-centering (SC) capability and stable energy dissipation under both loadings. Subsequently, two detailed finite element models were validated through the comparisons with experimental results in terms of global hysteresis loops and deformation shapes. The insights into the SMA-UD behavior under different directional loadings were presented. The influences of different geometric parameters of the SMA-UDs on the deformation mechanism were further highlighted. Parametric studies were carried out to investigate the effects of the existence of adjacent plates and the perpendicular compression on the SMA-UD's mechanical properties of practical interest in earthquake engineering. Results show that the adjacent plate has a positive role in the deformation mechanism of the SMA-UD under in-plane loading, whereas it has a slight effect on the SMA-UD under out-of-plane loading. The perpendicular compressive deformation undertaken by the SMA-UD itself can deteriorate its SC capability under in-plane loading. The results attained from this research are conducive to the design and applications of the SMA-UDs in engineering practice.